Exploring the purine core of 3′-C-ethynyladenosine (EAdo) in search of novel nucleoside therapeutics. Issue 8 (15th April 2016) - Hulpia, Fabian; Balzarini, Jan; Schols, Dominique; Andrei, Graciela; Snoeck, Robert; Van Calenbergh, Serge
Graphical abstract: Abstract: A series of new nucleoside analogues based on a C-3 branched ethynyl sugar derivative as present in 3′- C -ethynylcytidine (ECyd) and -adenosine (EAdo), combined with modified purine bases was synthetized and evaluated against a broad array of viruses and tumour cell lines. The pronounced cytostatic activity of EAdo was confirmed. EAdo and its 2, 6-diaminopurine analogue showed inhibitory activity against vaccinia virus (EC50 : 0.31 and 51 μM, respectively). Derivative10 on the other hand was found active against varicella zoster virus (EC50 : 4.68 μM).